Changes in macrophage-like cells characterized by en face optical coherence tomography after retinal stroke - Zeng, Yunkao; Wen, Feng; Mi, Lan; Ji, Yuying; Zhang, Xiongze (Frontiers in Immunology, 2022)
Purpose. The in vivo changes in macrophage-like cell(MLC) in acute ischemic retinal stroke remain unclear. Thus, the current study aimed to investigate the in vivo changes in MLC characterized by en face optical coherence tomography(OCT) after acute ischemic retinal stroke. Methods. Twenty patients with unilateral acute nonarteritic reperfused central retinal artery occlusion(CRAO) were participated in this study, and their contralateral eyes served as control group. A 3 μm en face OCT slab on the inner limiting membrane of the optic nerve head (ONH) region or macular region was used to visualize and binarize the MLCs. The MLCs were binarized and quantified using a semiautomated method. OCT angiography was used to evaluate the reperfusion status and obtain the structural data of the inner retina in the ONH and macula. The thickness of the ganglion cell complex in the macular region was measured. The optical intensity and optical intensity ratio of the inner retina were calculated to evaluate the ischemia severity. Results. In the ONH region, decreased vessel densities of radial peripapillary capillaries accompanied by increased thickness of the retinal nerve fiber layer were found in the CRAO eyes in comparison to the unaffected eyes(p=0.001, p=0.009, respectively). In the macular region, significantly lower vessel densities in both the superficial and deep capillary plexus and increased thickness of the ganglion cell complex were also found in the CRAO eyes(all p≤0.001). The ONH and macular MLC quantities and densities in CRAO eyes were significantly higher than those in the unaffected eyes(both p<0.001). Larger and plumper MLCs were observed in the CRAO eyes compared with their unaffected eyes. ONH and macular MLC densities were positively associated with the disease duration in the acute phase and the optical intensity ratio of inner retina. Conclusions. The increased density and morphological changes of MLCs may indicate the aggregation and activation of MLCs following acute reperfused CRAO. The aggregation of MLCs may be more pronounced in CRAO eyes with longer disease duration and more severe ischemia. MLCs characterized by en face OCT may serve as an in vivo visual tool to investigate neuroinflammation in the ischemic-reperfusion process of stroke.